Rancang Bangun Smart Home Security System Berbasis ESP32 dengan Multi-Sensor dan LCD I2C - Nada Candika; Raphael Maruli Simanjuntak; Riski Josua Pangaribuan; Eka Dodi Suryanto; Dian Putra Saragi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Home security is increasingly important due to risks such as theft, fire, and gas leakage. Conventional systems often lack real-time monitoring and automatic response. This study aims to design a smart home security system based on the ESP32 microcontroller using multiple sensors and an LCD I2C display. The system integrates a PIR sensor for motion detection, a magnetic door switch for door status, an MQ-2 sensor for gas detection, and a flame sensor for fire detection. A buzzer is used as an alarm, while a 16x2 LCD provides real-time system information. The method includes system design, hardware assembly, programming, and functional testing. The results show that the system can detect various hazards and provide immediate alerts through sound and display. This indicates that a low-cost, integrated security system can be effectively implemented for residential safety.